NEUROANATOMICAL MARKERS FOR EARLY DIAGNOSIS OF AUTISM SPECTRUM DISORDERS IN CHILDREN BASED ON NEUROIMAGING DATA (International journal of artificial intelligence, 2026)
Autism spectrum disorder is a heterogeneous neurodevelopmental condition whose first behavioral signs often emerge gradually, while formal diagnosis still depends primarily on clinical observation and developmental assessment. This gap between underlying brain change and visible symptom consolidation explains the growing interest in neuroimaging markers that may support earlier and more objective identification of risk. Current evidence suggests that the most promising neuroanatomical indicators are not isolated abnormalities in one brain area, but age-dependent developmental trajectories involving cortical surface area expansion, total brain volume growth, temporal and fusiform cortical alterations, atypical development of inferior frontal and midline structures, callosal changes, cerebellar differences, and abnormalities in white matter tracts.